Effectiveness of Animated Video Learning Media on Science Learning Outcomes of Elementary School Students - Dimas Qondias; Kale, Dominika Elviana; Tawa, Elisabeth Susanti; Ngura, Elisabeth Tantiana; Mere, Veronika Owa (UHN IGB Sugriwa Denpasar, 2024)
This study aims to examine the utilization of video media, specifically the effectiveness of animation media in improving science learning outcomes. The research method used in this article is qualitative descriptive research, where data is collected through literature reviews. The literature used in this research includes scientific articles related to the effectiveness of animated video learning media in enhancing the science learning outcomes of elementary school students. Data collection was conducted by searching for articles from national and international journals related to the research topic published between 2020 to 2024. This study identified 10 articles that align with the research focus, demonstrating the effectiveness of animated video learning media in improving science learning outcomes for elementary school students. Animated videos in science learning have been developed according to student needs, and currently, the effectiveness of animated videos yields positive results in supporting learning. Animated videos can increase student engagement and provide a more enjoyable learning experience. Therefore, the integration of animated videos into the learning process is an important step to support innovative and effective educational development.